Names and Naming in Young Adult Literature - Nilsen, Alleen Pace; Nilsen, Don L. F. (Rowman & Littlefield Publishers, 2007)
This book shows how authors of young adult literature use the creation of names for people, places, events, inventions, animals, and imaginary concepts as one of their most important literary techniques. Chapters address how authors use names to stretch readers' emotions, to reveal ethnic values and differences, to create 'other worlds,' and to establish tone. Other chapters focus on how authors use names to help readers remember who is who, such as J. K. Rowling in the Harry Potter books, or to communicate separate messages to adults and to young readers, as exemplified by Richard Handler in the Lemony Snicket books. Names and Naming in Young Adult Literature equips readers with the interest and the skill to make similar observations about names and naming when they read other books. Looking at the names an author has chosen to use is a wonderful first step in introducing readers to the concept of literary criticism as something to help readers get more pleasure and information from their reading. Public and school librarians, college instructors of young adult literature, teachers of creative writing, high school English teachers, and anyone else who is interested in young adult literature will find this book extremely interesting.